STUDENT PREPARATION FOR THE FINAL EXAMINATION SEMESTER AND ITS IMPLICATIONS IN GUIDANCE AND COUNSELING SERVICES - Engla Febrina Yenti; Afrizal Sano (Jurnal Neo Konseling, 2020)
The test is in principle as an evaluation tool to assess how far the knowledge has been mastered and the skills that have been acquired by students. The Final Semester Examination is a form of educational evaluation conducted by students to measure and assess student competencies so that the teacher can determine whether students can continue learning at a higher level or also known as grade promotion. When students face the Final Semester Exams, many students must prepare to start taking care of their body health because the condition of the body is the key to being able to concentrate on studying efficiently, preparing for good mental health, learning to be disciplined and responsible, diligent and centered, as well as serious in learning , study and repeat the lesson as best as possible all the material determined to be tested. Preparation for the Final Semester Examination is any activity or deed carried out by students to prepare for an exam that will be carried out at the end of the even semester or grade promotion test. The purpose of this study is to describe the preparation of students in facing the Final Semester Examination. This research uses the literature study method which obtained the results of previous research regarding the preparation of students in facing the Final Semester Examination.